Rapid Melt Growth of Single Crystal InGaAs on Si Substrates - Xue Bai; Chien-Yu Chen; Niloy Mukherjee; Peter B. Griffin; James D. Plummer (Advances in Materials Science and Engineering)
InGaAs integration on Si substrates is an important topic for next generation electronic devices. Rapid melt growth (RMG) has the potential to grow defect-free lattice mismatched materials on Si at low cost. Most previous publications have focused on growing binary III–V compounds by RMG, but none have discussed ternary compound materials. In this paper, we demonstrate the RMG of the single crystal ternary compound InGaAs on Si substrates. We discuss two main issues. The first is segregation along the stripe length. An analytical model is developed to describe the segregation of In/Ga in the grown stripe and the model is compared with experimental data. The second issue is the dissolution of the Si seed region during RMG, which leads to formation of Si islands inside the InGaAs stripe. The results of this study are applicable to any compound material in which Si is soluble at the elevated temperatures required for RMG.